The Influence of Learning Styles on Student Learning Outcomes at SMP 11 Kupang - Angelina Jayanti Saudale (Journal of Innovative and Creativity, 2026)
The study purpose was to examine the influence of students’ learning styles on learning outcomes at the junior secondary school level in Indonesia, with SMP Negeri 11 Kupang serving as a specific research context. Learning outcomes reflect students’ achievement levels in understanding instructional processes, while learning styles represent individual differences in processing information. Understanding this relationship is essential to improve instructional effectiveness and academic achievement. Materials and methods. This study employed a quantitative approach using an ex post facto research design. The ex post facto method was selected because the independent variable, students’ learning styles, had already occurred naturally and was not manipulated by the researcher. The research sample consisted of 20 junior high school students selected as research subjects. Data on learning styles were collected using a questionnaire, while learning outcomes were obtained from students’ semester report scores. The data were analyzed using descriptive statistics, Pearson correlation analysis, and simple linear regression to determine the relationship and influence between variables. Results. The findings revealed a positive and significant relationship between learning styles and students’ learning outcomes. Statistical analysis indicated that learning styles contributed 21.3% to variations in learning outcomes, while the remaining percentage was influenced by other factors beyond this study. Conclusions. It can be concluded that learning styles have a significant influence on students’ learning outcomes. Therefore, teachers are encouraged to consider students’ learning styles when designing instructional strategies to enhance learning effectiveness and academic performance.